In video war games, are military personnel’s fixation patterns different compared with those of civilians? - Söderberg, Håkan; Khalid, Junaid; Rayees, Mohammed; Dahlman, Joakim; Falkmer, Torbjorn (Sage Publications, Inc., 2012)
For combat personnel in urban operations, situational awareness is critical and of major importance for a safe and efficient performance. One way to train situational awareness is to adopt video games. Twenty military and 20 civilian subjects played the game “Close Combat: First to Fight” on two different platforms, Xbox and PC, wearing an eye tracker. The purpose was to investigate if the visual search strategies used in a game correspond to live training, and how military-trained personnel search for visual information in a game environment. A total of 27,081 fixations were generated through a centroid mode algorithm and analyzed frame-by-frame, 48% of them from military personnel. Military personnel’s visual search strategies were different from those of civilians. Fixation durations were, however, equally short, that is, about 170 ms, for both groups. Surprisingly, the military-trained personnel’s fixation patterns were less orientated towards tactical objects and areas of interest than the civilians’; the underlying mechanisms remaining unclear. Military training was apparently not advantageous with respect to playing “Close Combat: First to Fight”. Further research within the area of gaming, military training and visual search strategies is warranted.